2013
DOI: 10.1371/journal.pone.0075575
|View full text |Cite
|
Sign up to set email alerts
|

Adult Attention Deficit Hyperactivity Disorder and Violence in the Population of England: Does Comorbidity Matter?

Abstract: BackgroundIt is unclear whether the association between Attention Deficit/Hyperactivity Disorder (ADHD) and violence is explained by ADHD symptoms or co-existing psychopathology. We investigated associations of ADHD and its symptom domains of hyperactivity and inattention, among individuals reporting violence in the UK population.MethodsWe report data from the Adult Psychiatric Morbidity Survey (2007), a representative sample of the household population of England. A randomly selected sample of 7,369 completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…T. Wymbs et al, 2014), the sample consisted of 100% males; in the study of Crane et al, the percentage of ADHD males was not reported. Gonzalez et al (2013) reported an increased risk for adult ADHD on the outcome of all forms of violence, including DV and IPV. However, when controlled for adult ASPD, the significant effects of adult ADHD and Inattentive (IA) symptoms were lost.…”
Section: Results Of the Case Control Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…T. Wymbs et al, 2014), the sample consisted of 100% males; in the study of Crane et al, the percentage of ADHD males was not reported. Gonzalez et al (2013) reported an increased risk for adult ADHD on the outcome of all forms of violence, including DV and IPV. However, when controlled for adult ASPD, the significant effects of adult ADHD and Inattentive (IA) symptoms were lost.…”
Section: Results Of the Case Control Studiesmentioning
confidence: 99%
“…The other researchers only used a few (one to three) questions regarding frequency of DV/IPV. Fifth, comorbid diagnoses (other than CD/ASPD) were only addressed as a confounder in the study of Crane et al (2014) and Gonzalez et al (2013) and not in the other studies. Finally, in none of the studies, information was provided about medication use.…”
Section: Limitations and Strengths Of The Findingsmentioning
confidence: 99%
“…Participants were asked about their violent behavior ("have you been in a physical fight, assaulted or deliberately hit anyone in the past 5 years"), as used in previous UK surveys of violence (Coid et al, 2006;Gonzalez, Kallis, & Coid, 2013). All participants were queried regarding their violent behavior with the initial question: "Have you been in a physical fight, assaulted, or deliberately hit anyone in the past five years?".…”
Section: Violence Outcomesmentioning
confidence: 99%
“…Aggression is common in many disorders co-morbid with AD/HD, in particular personality disorders (Dowson, 2006), and it has been argued that the best response to aggression in the context of AD/HD is to treat the comorbid disorders (Gonzalez, Kallis & Coid, 2013).…”
Section: Introductionmentioning
confidence: 99%